“Why Are You Running Away From Social Media?” Analysis of the Factors Influencing Social Media Fatigue: An Empirical Data Study Based on Chinese Youth - He, jianping; Liu, Yixuan (Frontiers in Psychology, 2021)
In the digital era, social media is increasingly permeating the fragmented lives of people. While enjoying the convenience and speed of online socializing, people are gradually surrounded by a variety of information. Through observations and interviews, we found that young people are plagued by negative comparisons, interaction dysfunction, information overload, social overload, and intergenerational communication in the process of participating in social media. Increasing numbers of young people feel overwhelmed in the process of online socialization and the phenomenon of social media fatigue (SMF) gradually spreads. This study combined the existing relevant theoretical models of the influencing factors of SMF and the real-life empirical materials of youth groups. Furthermore, this study enriched into new research variables and validated the data of relevant variables through a questionnaire survey (n = 663) to explore the influencing factors of SMF of youth groups and inductively analyze the inner logic of the emergence of SMF among such groups. It was found that negative comparison, interaction dysregulation, information overload, social overload, self-efficacy, and impression management all had significant positive effects on SMF behaviors, while privacy anxiety and intergenerational communication had no significant positive effects on SMF behaviors.